2019
DOI: 10.1515/chem-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Water Fluoride with Body Fluids, Dental Fluorosis and FT4, FT3 –TSH Disruption among Children in an Endemic Fluorosis area in Pakistan

Abstract: In the present study 134 children were studied for comparison and correlation between an endemic fluorotic village Rukh Mudke (RM), n = 74, and a non-fluorotic village Ottawa (OTW), n = 60. The children were aged between 7-18 years and selected for the estimation of fluoride in their household water, body fluids (urine-serum), dental fluorosis and thyroid hormones (Free tri-iodothyronine (FT3) free tetra iodothyronine (FT4) and thyroid stimulating hormone (TSH) respectively. Mean concentration of water fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Clinically, elevated TSH levels often correlate with reduced T3 and T4 production, indicating a response to hormone deficiency and a need for increased production and release. This pattern was observed in studies by Khandare, Validandi [ 23 ] and [ 24 , 25 ], although [ 22 ] reported no such correlation. Moreover, while an increase in PTH is relevant, it does not directly influence thyroid functions.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Clinically, elevated TSH levels often correlate with reduced T3 and T4 production, indicating a response to hormone deficiency and a need for increased production and release. This pattern was observed in studies by Khandare, Validandi [ 23 ] and [ 24 , 25 ], although [ 22 ] reported no such correlation. Moreover, while an increase in PTH is relevant, it does not directly influence thyroid functions.…”
Section: Discussionsupporting
confidence: 62%
“…The studies did not categorize participants according to life stages, such as childhood, adolescence, adulthood, middle age, or senior years. Wang, Wang [ 22 ], Kutlucan, Koroglu [ 15 ], Khandare, Validandi [ 23 ], Zulfiqar, Rehman [ 24 ] and Zulfiqar, Ajaz [ 25 ] evaluated participants ranging in age from 7 to 18 years. Conversely, Leone, Leatherwood [ 20 ] focused on adult and older individuals, with ages ranging from 18 to 60 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, T3 incorporation may be diminished, resulting in the production of prolactin TSH, which limits thyroid iodine absorption by fuorine. As a result, both the secretion of T4 and the stimulating impact of exogenous THS are diminished [23][24][25]. Studies in this area have revealed that enhanced consumption of fuoride in drinking water causes changes in hormones related to thyroid function (TSH, T3, FT3, T4, FT4, and rT3) and adjustments in the actions of deiodinase enzymes [5,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Dental fluorosis and skeletal fluorosis are major public health concerns around the world. Regions with a high prevalence of such illnesses have been recently documented in Asia, particularly in China [1][2][3][4], India [5][6][7][8], Pakistan [9][10][11], and Sri Lanka [12][13][14]. In Africa, dental fluorosis is prevalent mainly in Sub-Saharan countries, including Kenya, Tanzania, Uganda, Ethiopia, Eritrea, Sudan, Ghana, Malawi, Niger, Nigeria, Mozambique, and South Africa [15][16][17].…”
Section: Introductionmentioning
confidence: 99%